The Implementation of Flipped Classroom Using Moodle to Increase Students’ Mathematics Creative Thinking from Learning Style Viewpoint - Siti Nurelis Sutiani; Ricki Yuliardi (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aimed to describe the success of flipped classroom using Moodle to increase students’ creative thinking abilities in view of learning styles. This study used quasi-experiment non-equivalent control group design with the participants consisted of 72 students of SMA Negeri 1 Ciawigebang in the academic year of 2022/2023 who 36 XD students as the experimental group and 36 XC students as the control group. The instruments used were tests and questionnaires. The results of data analysis with significance level of 5% revealed that on the learning model factors obtained values 0.012 < 0.05 with the conclusion that there were differences in the ability to think creatively between students who are given flipped classroom using Moodle and conventional learning. N-Gain score in the experimental class is 0.6153 while the control class is 0.3803. Hypothesis testing on learning style factors has value 0.766 > 0.05 with the conclusion that there were no differences in the ability to think creatively between students with visual, auditory, and kinesthetic learning styles. Interaction diagrams shows that visual students are better suited to learning with flipped classroom using Moodle models and auditory students are better suited to learning with conventional models